Examining the Influence of Career Motivation, Financial Rewards, and Student Perceptions on Public Accounting Career Interest: A Study of Accounting Students in Lamongan Regency - Lazuardi, Yanuar; Rofiqoh, Izzatul (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
Public accountants are a profession that plays an important role in ensuring transparency and accountability of financial reports through the provision of audit services, tax consultations, and other financial services independently to clients, both individuals and companies. This profession offers challenges as well as promising career opportunities, especially for graduates of accounting study programs. This study aims to investigate the influence of career motivation, financial rewards, and student perceptions on students' interest in becoming public accountants. The research utilized a quantitative methodology based on primary data collection. The data were gathered using survey questionnaires administered to 100 accounting students from Lamongan Regency, who were chosen through purposive sampling techniques. The method of analysis utilized was the use of multiple linear regression in combination with IBM SPSS 25 software. Findings suggest that factors such as career motivation, financial incentives, and student viewpoints play a crucial role in shaping the career interests of individuals pursuing a career in public accounting, both individually and collectively.